Academic Life in Emergency Medicine (ALiEM) Blog and Podcast Watch: Infectious Disease Emergencies - Roppolo, Lynn (Cureus, 2018)
To address the needs for curation of online educational content as well as the development of a nationally available curriculum that meets individualized interactive instruction, the Academic Life in Emergency Medicine (ALiEM) Approved Instructional Resources (AIR) Series and AIR-Pro Series were created in 2014 and 2015, respectively. Using an expert-based, crowd-sourced approach, these two programs identify trustworthy, high-quality, educational blog, and podcast content. Here, we summarize the accredited posts that met our a priori determined quality criteria and evaluated by eight attending physicians.